One more tool for the food aid toolbox? Experimental evidence on food aid packaging. (October 2019) - Brennan, Mark; Sundar, Prithvi; Goentzel, Jarrod; Frey, Daniel; Mathias, Joanne
Highlights: Much of in-kind food aid has been modernized, but packaging remains unchanged. We estimate the effect of new packaging on shipment quality, cost, and timeliness. New materials maintain shipment quality and cost, while improving timeliness. Avoided fumigation and handling seem to drive cost differences. Food assistance tools must be used in complimentary ways. Abstract: International food assistance reaches more than 90 million people per year, much of it through in-kind programs that distribute food. Several key aspects of in-kind programs—what food is shipped, when and from where it is sourced—have been changed to improve program effectiveness and efficiency, becoming helpful tools in the modernized in-kind food assistance toolbox. Packaging—in what food is shipped—remains an unstudied and underused tool despite more than 50 million bags per year passing through in-kind supply chains, affecting program effectiveness and efficiency. We conduct an experiment with 46 shipments using different packaging materials and sizes to measure the effect of packaging on shipment quality, cost, and timeliness. Analyzing the data with randomization tests, we find that, relative to the current materials, new materials maintain shipment quality and cost while improving timeliness and in some cases may reduce cost. One promising material that balances cost and effectiveness is a bag with a biopesticide applied, designed to prevent insects from reproducing. We also find that, relative to the current size, larger bags may improve costs at least in the domestic portion of the supply chain. Donors and their partners should consider packaging as one more tool in the modernized food assistance toolbox. As the toolbox continues to fill, the coming opportunity and challenge to identify situations where the various tools work in complementary ways.